2013
DOI: 10.1007/s12311-013-0462-2
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Circuits Underlying Cerebellar Modulation of Prefrontal Cortical Dopamine in Mouse Models of Autism Spectrum Disorder

Abstract: Imaging, clinical and pre-clinical studies have provided ample evidence for a cerebellar involvement in cognitive brain function including cognitive brain disorders, such as autism and schizophrenia. We previously reported that cerebellar activity modulates dopamine release in the mouse medial prefrontal cortex (mPFC) via two distinct pathways: (1) cerebellum to mPFC via dopaminergic projections from the ventral tegmental area [VTA] and (2) cerebellum to mPFC via glutamatergic projections from the mediodorsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 59 publications
(58 reference statements)
0
51
1
1
Order By: Relevance
“…Cerebellar co-activation with regions of the pre-SMA, SMA, and cingulate motor areas indicates involvement with the cognitive control and execution of motor actions (Akkal et al, 2007; Nachev et al, 2008; Amiez and Petrides, 2014), while regions in the anterior cingulate and insular cortices exhibit involvement in error-processing and subsequent behavioral adjustments (e.g., Danielmeier et al, 2011). Furthermore, motor responses are critically associated with dopaminergic function (Durieux et al, 2011; Rogers et al, 2013), as is error-processing (Holroyd et al, 2002). Involvement in these motor and cognitive functions is consistent with theories highlighting a role of the cerebellum in regulating dopaminergic function and serving as a forward controller and toggling cortical circuits between automatic and controlled processes (Dosenbach 2006; Ramnani 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar co-activation with regions of the pre-SMA, SMA, and cingulate motor areas indicates involvement with the cognitive control and execution of motor actions (Akkal et al, 2007; Nachev et al, 2008; Amiez and Petrides, 2014), while regions in the anterior cingulate and insular cortices exhibit involvement in error-processing and subsequent behavioral adjustments (e.g., Danielmeier et al, 2011). Furthermore, motor responses are critically associated with dopaminergic function (Durieux et al, 2011; Rogers et al, 2013), as is error-processing (Holroyd et al, 2002). Involvement in these motor and cognitive functions is consistent with theories highlighting a role of the cerebellum in regulating dopaminergic function and serving as a forward controller and toggling cortical circuits between automatic and controlled processes (Dosenbach 2006; Ramnani 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lurcher/chimeric mice, which display impaired working memory and inflexibility behaviors, demonstrate abnormalities in distributed neuronal circuitry from cerebellum to medial prefrontal cortex. Fragile X mutant mice demonstrated disrupted cerebellarecortical circuitry that approximates the disruption seen in Lurcher chimeric animals, implicating disruption of these distributed circuits in ASD behaviors [47]. However, a functional contribution of these neuronal circuits to ASD behaviors remains to be determined.…”
Section: Distributed Cerebellar Circuitry In Asdmentioning
confidence: 99%
“…Mouse models demonstrate similar anatomic deficits with the naturally occurring Lurcher mutant mouse (which possesses a Grid2 mutation) demonstrating significant cerebellar neuronal loss in addition to behavioral ataxia. Lurcher chimeric animals also display working memory deficits and cognitive inflexibility in addition to disrupted circuitry from cerebellar hemispheres to medial prefrontal cortex [47].…”
Section: Grid2mentioning
confidence: 99%
“…Deficits in the dopamine system have been demonstrated in both fragile X animal models and patients (Roberts et al, 2005; Wang et al, 2008b; Weinshenker and Warren, 2008; Fulks et al, 2010; Paul et al, 2013; Rogers et al, 2013). Electrophysiological studies have found that dopaminergic modulation of synaptic transmission and potentiation are impaired in fragile X mice (Wang et al, 2008b; Paul et al, 2013).…”
Section: Targeted Pharmacotherapy For Fragile X Syndromementioning
confidence: 99%